Формирование вовлеченности сотрудников в работу предприятий - Брюховецкая, Н.Е.; Черная, А.А. (Стратегія і механізми регулювання промислового розвитку, 2013)
Уточнена сущность понятий удовлетворенности, лояльности и вовлеченности сотрудников, обосновано использование их в исследованиях процессов развития персонала и формирования человеческого капитала предприятий. Установлено, что ключевым понятием, которому предшествуют удовлетворенность сотрудников работой и лояльность по отношению к предприятию, является вовлеченность сотрудников в работу. Определены факторы, влияющие на формирование вовлеченности. Обоснованы предложения по формированию вовлеченности сотрудников в работу предприятий. Уточнено сутність понять задоволеності, лояльності й залученості співробітників, обґрунтовано використання їх у дослідженнях процесів розвитку персоналу і формування людського капіталу підприємств. Встановлено, що ключовим поняттям, якому передують задоволеність співробітників роботою і лояльність щодо підприємства, є залученість співробітників у роботу. Визначено чинники, що впливають на формування залученості. Обґрунтовано пропозиції щодо формування залученості співробітників у роботу підприємств. The essence of the concepts of employees’ satisfaction, loyalty and involvement is clarified, their use in research on processes of staff development and human capital formation of enterprises is justified. It was established that the key concept that follows job satisfaction of the employees and loyalty to the company is the involvement of employees in the work. The involvement of employees is determined by motivation. It is an important factor in the functioning of the enterprise and an internal emotional readiness to make further efforts to achieve the goals of the enterprise with its own wish and initiative. The factors influencing the formation of involvement are defined. The important aspect of consistency is theinvolvement, particularly of employees and managers that allows employees to unite voluntarily in order to perform their tasks and achieve the desired results. The proposals on the formation of involvement of employees in the operation of enterprises are grounded. For example, in the process of management of a modern enterprise’s personnel and formation of employees involvement appropriate is to establish two-way communication with employees (Intranet, meetings, interviews, questionnaires). The employees should understand that their own opinion is important for creating the intra-institutional environment of the enterprise and for improving its operation; it will help to enhance communication, build consistency in the workplace. It is necessary to inform and explain the reasons for changing goals, establish communication between managers and employees, involve and coordinate employees, encourage their desire to achieve the goals of the enterprise, encourage creative work, proposals, ideas, ability to take responsibility providing that the work is performed according to employees’ job descriptions. It is also necessary to give them credible and reliable information about the corporate culture, career prospects and conditions of salary growth.